Hiperplasia Angiofolicular (doença de castleman): a propósito de um caso - Monteiro, Miguel Cardim (2023)
A report of a case of angiofolicular hyperplasia in a lymphnode is presented. Diagnosis was based on the hystopathologic findings. Considerations about the bioiogical behavior and possible etiologic mechanisms implied are made and a short review of the literature and of the patient's clinical course is also presented.